PENGARUH PENGUNGKAPAN EMISI KARBON TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATOR (Studi Empiris pada Perusahaan yang Terdaftar dalam Indeks KOMPAS100 Periode 2022-2024) - M. Sabbit Qolbi; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2026)
This study aims to examine and analyze the effect of carbon emission disclosure on firm financial performance, as well as to evaluate the potential moderating role of firm size in this relationship. The measurement of financial performance in this study is classified into two dimensions, namely accounting-based financial performance (Return on Assets/ROA) and market-based financial performance (Tobin’s Q).This study uses a quantitative approach with secondary data sourced from annual reports and sustainability reports. The research population includes companies listed on the Indonesia Stock Exchange (IDX) in the KOMPAS100 Index during the 2022–2024 period. The sampling technique used was purposive sampling, which resulted in a final sample of 59 non-financial companies with a total of 177 units of analysis. Data analysis was conducted using panel data regression with the Fixed Effect Model (FEM) approach through EViews 14 software.The results indicate that carbon emission disclosure has a negative and significant effect on firm financial performance, both from an accounting (ROA) and market (Tobin’s Q) perspective. However, the moderation test results show that firm size significantly moderates and changes the direction of the effect to be positive.